Leveduras como agentes de controle de Alternaria alternata em tomates no pós-colheita: mecanismos, resistência a estresses e formulação - Bosqueiro, Ariane Silva (Universidade Federal de São Carlos, 2019)
The fungus Alternaria alternata causes rot in several post-harvest crops, limiting commercialization and causing damage to the entire agricultural production chain. The use of biological control agents has been an alternative and the yeasts have characteristics that make them suitable for this use. Understanding the mechanisms of action used by these yeasts, their resistance to different stresses and finding formulations that guarantee their viability and a good control activity of phytopathogenic fungus, are important aspects to be clarified in this type of approach. The objectives of the present work were to evaluate the mechanisms of action of the yeasts Torulaspora globosa (strain 5S55) and Trichosporon asahii (strain 3S44) involved in the biological control activity, the resistance of these yeasts under different stress sources and their efficiency in formulations in the control fungus Alternaria alternata in tomato. For this, the two strains were tested for the mechanisms of action: production of hydrolytic enzymes (chitinase and β-1,3-glucanase), volatile organic compounds (VOCs) in vivo test and biofilm formation. Strains culture was evaluated under stress conditions, including different temperatures (10, 20 and 30 °C), osmotic stress (0, 3, 6 and 9% NaCl), oxidative stress (0, 10, 20, 30 and 40 mM H2O2) and resistance to mancozeb-based fungicide Manzate WG® (0,1, 0,2, 0,3, 0,4 and 0,5 mg/mL). Formulations containing corn starch and gelatin at 2% were evaluated for adhesion of the yeasts on the fruit surface and, later, the formulation with starch was evaluated in tomatoes to control A. alternata. As a result, the strains presented results only in the production of the enzyme β-1,3-glucanase, and T. asahii (3S44), also presented activity for the formation of biofilm in the in vitro test. T. asahii (3S44) showed to be more resistant than T. globosa (5S55) in all tests, being that the condition that most affected the viability of both strains was oxidative stress. In addition, none could withstood the minimum concentration of mancozeb-based fungicide. The formulation that showed the best result in the fixation of the cells on the tomato surface was with corn starch. When this was used in the control of A. alternata, it showed 15,7 and 42,5% inhibition with T. globosa (5S55) and T. asahii (3S44), respectively. In view of such results, it is possible to state that T. asahii (strain 3S44) presented, in general, better results in relation to T. globosa (strain 5S55) and that both have potential for biological control.
Yeasts as Alternaria alternata control agents on tomatoes post-harvest: mechanisms, resistance to stresses and formulation
Keywords: Controle biológico; Enzimas hidrolíticas; Produção de COVs; Biofilme; Estresses ambientais; Formulação; Biological control; Hydrolytic enzymes; VOCs production; Biofilm; Environmental stresses; Formulation; CIENCIAS AGRARIAS::AGRONOMIA; CIENCIAS AGRARIAS; CIENCIAS BIOLOGICAS::MICROBIOLOGIA